DIAGNOSTIC ROLE OF LIPOPROTEIN (A) IN TYPE-2 DIABETES MELLITUS - SANJEEDA TABASUM. M, (International Journal of Pharma and Bio Sciences, 2013)
To evaluate lipoprotein (a) in Diabetic population for the diagnostic role as a cardiac risk biomarker.Materials & Methods: A total of 302 subjects included in a case control study, of 198 diabetic and 104 controls, who were sex and age matched and non-alcoholic. Serum total cholesterol and triglyceride, HDL Cholesterol were measured using Siemens kits and Lp(a) measured using Agappe kit analysed on Chem 200 automated analyser. Results & Discussions: Patients were gender matched with p-value=0.273. Sugar parameters with significant results of p-value 0.001** and mean value of FBS being 169.09±82.44 mg/dL and PPBS mean being 267.17±102.75 mg/dL compared to control group. Lipid parameters have shown total cholesterol mean of diabetic group being 294.94±110.48 mg/dL and 202.36±50.48 mg/dL with the p being 0.001** and triglyceride mean being 273.77±148.27 mg/dL, control being 112.05±39.16 mg/dL with the p value 0.001**. HDL: LDL has also shown significant value of p being 0.001**. SGOT (AST) mean of diabetic group127.22 ±10.26 U/L and normal control 25.23±U/L and SGPT (ALT) mean of diabetics 30.29±11.22U/L, control mean 26.65±7.5U/L the p-value 0.003**.Lipoprotein (a) has shown significant levels in diabetic population of mean being 36.89±11.18U/L showing significance of p=<0.001**.Hence can be called in short as cardiac risk biomarker.